Chemical immobilization of African elephant in lowland forest, southwestern Cameroon - Elkan, Paul; Planton, Hubert; Powell, James; Haigh, Jerry; Karesh, William (Pachyderm, 1998)
Undertaken in the lowland forest of southwestern Cameroon, as part of a long term investigation of elephant ecology, this study was the first one to immobilize and radio collar free ranging forest elephants. The paper reviews the difficulties encountered in the December 1990-April 1993 study during which six immobilizations (out of 12 reviewed attempts) were completed, however two of the darted animals were dead when located. Etorphine and carfentanil were used as immobilizing agents. Dense vegetation, diverse topography and severe climatic conditions caused the darting and post-darting location of the subject animal to be difficult and hazardous to both man and elephant. Innovation in both methodology and strategy occurred as various delivery systems and technological aids were field tested, the lessons learned should prove useful in undertaking large mammal immobilization under dense forest conditions.